The professional career of sociologists : a graphical chain model reflecting early influences and associations - Pigeot, Iris [Verfasser]; Heinicke, Astrid [Verfasser]; Caputo, Angelika [Verfasser]; Brüderl, Josef [Verfasser] (My University, 2000)
"Currently, German universities take great interest in how their students perform in later professional life. Information on early determinants of success is needed in order to adjust educational programs and to cope more easily with the expected increase in the number of students in the coming years. In this paper we analyse data on the occupational careers of sociologists. The complexity of the underlying research question is taken into account by modelling the associations using so-called graphical chain models. These models are in general constructed such that conditional independencies can be concluded from the corresponding graph. We present the different steps in formulating the dependence structure. For checking its appropriateness, a model selection strategy is applied based on regression techniques. The final graph gives essential hints with respect to early determinants for professional success." (author's abstract, IAB-Doku)
Keywords: S 6.4.6.2 Wissenschaftliche Berufe; G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; G 1.1.4 Statistiken zu speziellen Problemlagen & Bereichen; T 3.5 Statistik; Soziologe; Berufsverlauf; Berufsproblem; Statistische Methode; Modellentwicklung